A Fiqh al-Mu'amalat Analysis of the Ijarah Contract in Digital-Based Turnitin Services: Analisis Fiqih Muamalah Terhadap Akad Ijarah Dalam Layanan Jasa Turnitin Berbasis Digital - afifahdwi cahyanti; Muhammad Ufuqul Mubin (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2026)
This study examines the practice of digital Turnitin checking services from the perspective of the ijarah contract in Islamic jurisprudence (fiqh muamalah). The background to this research arises from the need to increase academic integrity through authenticity testing of scientific papers, which is now often conducted online, raising questions about the suitability of these digital transactions with Sharia principles. The research problem is directed at how the practice of digital Turnitin services can be understood as an ijarah contract and to what extent it meets the pillars and requirements of Sharia, particularly the clarity of the service object, fairness of wages, and mutual consent between the parties. The research method uses a descriptive qualitative approach with data collection techniques consisting of literature studies and questionnaires distributed to service users. Data analysis was conducted narratively based on the principles of muamalah and respondent responses to describe the dynamics of this digital service transaction. The results show that the Turnitin checking service has fulfilled the principles of the ijarah contract, starting from the clarity of service benefits in the form of inspection reports, approvals, and transparent wage agreements, as well as fairness and mutual consent between the parties. Respondents generally assessed this service as compliant with Sharia principles, particularly in terms of fairness, transparency, and transaction security. Thus, this study concludes that the ijarah contract can be applied to modern digital transactions and supports the development of contemporary muamalah literature. This study also underscores the importance of improving public understanding of the ijarah contract in the context of digital services to ensure that transactions are more compliant with Sharia principles and provide sustainable benefits.